Technological aspects of obtaining structured emulsions in composition of minced meat products - Нечепуренко, Кристина Борисівна; Пивоваров, Павло Петрович (Eastern-European Journal of Enterprise Technologies, 2014)
The nutrition structure that has developed inUkrainetoday dictates the need to expand the range of culinary products by more efficient use of plant products, to which still little attention has been paid. The problems of the lack of nutrients with high biological value in nutrition of a modern man are shown in the paper. The studies in this field are first given in the paper, and it was proved that a promising raw material for producing such products is the use of structured products, the use of which lies in the basis of alginate emulsions with calcium residues. The studies of the rheological properties of the structured emulsions and physico-chemical aspects of obtaining the latter in the composition of minced meat products are given in the paper. The use of a wide range of new technologies, including emulsification of various raw materials, namely polysaccharides for the production of fundamentally new products, which are characterized by high biological value, is submitted for consideration. As a result of the studies, structural and mechanical properties of the model systems and physico-chemical indices were determined. These data allow presenting the technology, ready for introducing to the technological process of obtaining emulsions in minced meat composition. This technology will allow obtaining products not only with standardized indices, but also overtaking the organoleptic indicators of quality that facilitate the production process.